Scalable nanoconfined GO/SWCNT-OH membranes for efficient high-salinity organic wastewater treatment - Yechen An; Xiaoxu Gao; Jing-Long Han; Yuting Ning; Xinping Fu; Ruiyun Ren; Liang Mei; Wenli Jiang; Ruifeng Yan; Jun Cui; Yu Tao; Aijie Wang (Water Research, 2026)

Methanol vehicles with low PN23 emissions may still exhibit a potential SubPN23 particle burden - Jie Yao; Xinping Yang; Yitu Lai; Wanyou Luo; Hongfei Chen; Yunjing Wang; Xin Li; Mingliang Fu; Hang Yin; Yan Ding (Journal of Cleaner Production, 2026)

Modulating Ti-O-Bi-based charge transport channels across Bi6O7/Ti3C2Tx interface for augmented targeted iodide ion removal via capacitive deionization - Nan Feng; Xinping Fu; Mingxing Liang; Yuting Ning; Chenghao Li; Tongtao Fan; Huan Zhang; Wei Yao; Donghai Yuan; Jun Cui (Chemical Engineering Journal, 2026)

Phase-modulated engineering of oxygen-doped molybdenum disulfide for boosting visible light-driven photocatalytic tetracycline degradation - Ze Yuan; Chenghao Li; Nan Feng; Xinping Fu; Yuting Ning; Wei Yao; Lepu Ci; Jun Cui (Journal of Environmental Chemical Engineering, 2026)

Efficient depolymerization of polyethylene terephthalate fabric under mild conditions and recycling of polyester/cotton blended fabric - Xinping Li; Jinying Fu; Yanyan Guo; Xingyan Wu; Jing Xu; Rongliang Wu; Huaping Wang; Fuyou Ke; Ye Chen (Journal of Environmental Chemical Engineering, 2026)

Trajectory optimization for unknown maneuvering target tracking with bearing-only measurements - Yingbo Fu; Ziwen Yang; Liang Xu; Yi Guo; Shanying Zhu; Xinping Guan (Ocean Engineering, 2026)

Formaldehyde emissions from light-duty gasoline vehicles: Emission characteristics and future trends - Junchao Zhao; Xinping Yang; Zhining Zhang; Mingliang Fu; Yunjing Wang; Songdi Liao; Zhipeng Tu; Lijuan Qi; Xiaotong Wang; Zhenyu Luo; Hang Yin; Yan Ding (Journal of Hazardous Materials, 2025)

Regulating electronegativity difference and piezoelectric strain of the Mo-S-Mo structure via introducing S vacancies for boosting piezo-photoelectric activity - Yanjiao Li; Yuting Ning; Xinping Fu; Yu Jiang; Lianfeng Wang; Jun Cui (Journal of Environmental Chemical Engineering, 2025)

Shear damage characteristics and model study of yellow sandstone structure surfaces after high-temperature treatment - Fu Zheng; Annan Jiang; Xinping Guo; Haopeng Jiang (Bulletin of Engineering Geology and the Environment, 2025)

Evaluation of real-world CO2 and NOX emissions of various in-use heavy-duty vehicles - Jia Ke; Han Jiang; Xinping Yang; Mingliang Fu; Zhihui Huang; Yunjing Wang; Yan Ding (Journal of Hazardous Materials, 2025)

Interfacial polarization-induced microwave pyrolysis for expeditious municipal solid waste transformation and valorization - Wenliang Wang; Hui Miao; Hangzhuo Li; Yangyi Cui; Yishuai Fu; Xinping Li; Lei Chen; Bailiang Xue; Chao Duan; Weikun Jiang (Chemical Engineering Journal, 2025)

Single-cell dynamic RNA and glycosylation sequencing reveals the mechanism underlying the differentiation of pluripotent stem cells into hematopoietic stem cells - Wanyi Feng; Sheng Zeng; Donghui Liu; Wei Gong; Junjie Hu; Weihua Xu; Zhichao Ma; Shengmiao Fu; Xinping Chen (Human Cell, 2025)
Studying the mechanism of hematopoietic stem cells’ generation from induced pluripotent stem cells in vitro can be useful for understanding embryonic hematopoiesis, as well as for the application of related cell therapy. This study aimed to delineate the process of the differentiation of induced pluripotent stem cells into hematopoietic stem cells’ models and provide a theoretical basis and clinical value for the production of hematopoietic stem cells in vitro. We analyzed the differentiation model by single-cell dynamic transcriptome and glycosylation sequencing, which was divided into three differentiation stages based on the new‐to‐total RNA ratio and glycosylation level. Two differentiation fates were found in the pseudo-time, including hematopoietic development and other tissue development. Precursor hematopoietic cells with a high glycosylation level greatly expressed hematopoietic regulation and vascular endothelial genes, suggesting that glycosylation is associated with angiogenesis and hematopoietic regulation. The multiple differentiation events in the in vitro model are similar to those in hematopoietic development in vivo, including yolk sac hematopoiesis, cellular communication between non-potential hematopoietic subsets and potential hematopoietic subsets, gene expression, and temporal deviations in hematopoietic fate. Our study has revealed the similar hematopoiesis process in the differentiation model via single-cell dynamic RNA and glycosylation sequencing, which provides an important theoretical basis for the study of hematopoietic stem cell development.

Distribution characteristics of Hg and As in the water-SPM system in the Xiaoqing river estuary and coastal - Feifei Zhang; Dong Zhang; Xiaoyue Li; Huawei Lou; Hongrui Fu; Xiaojun Sun; Peiyan Sun; Xinping Wang; Mutai Bao (Marine Environmental Research, 2025)

Revisiting the estimation indicator for HONO emissions from light-duty vehicles - Xinping Yang; Mingliang Fu; Songdi Liao; Zhipeng Tu; Weijie Feng; Yunjing Wang; Han Jiang; Qili Tian; Hang Yin; Junyu Zheng; Yan Ding (Journal of Hazardous Materials, 2024)

Evaluation of the accuracy of remote emission sensing measurements via real-world vehicle dynamic tests - Qili Tian; Xinping Yang; Han Jiang; Xiaohu Wang; Jin Liu; Yingzhi Zhang; Yang Cao; Yu Kang; Mingliang Fu; Hefeng Zhang (Environmental Pollution, 2024)

A thermoresponsive metabolic nanomodulator for achieving photochemotherapy-sensitized cancer immunotherapy - Shun-Yu Wu; Xiao-Yu Zhu; Xinping Zhang; Yong-Xi Zhou; Shao-Zhe Wang; Yan-Hong Li; Shi-Jie Hao; Tian-Yu Wang; Xin-Wang Yu; Yuxin Guo; Guang-Yu Pan; Bin Xu; et al. (Chemical Engineering Journal, 2024)

Co-pollution risk of petroleum hydrocarbons and heavy metals in typically polluted estuarine wetlands: Insights from the Xiaoqing River - Feifei Zhang; Hongrui Fu; Dong Zhang; Huawei Lou; Xiaojun Sun; Peiyan Sun; Xinping Wang; Mutai Bao (Science of The Total Environment, 2024)

Aβ-Aggregation-Generated Blue Autofluorescence Illuminates Senile Plaques as well as Complex Blood and Vascular Pathologies in Alzheimer’s Disease - Hualin Fu; Jilong Li; Chunlei Zhang; Peng Du; Guo Gao; Qiqi Ge; Xinping Guan; Daxiang Cui (Neuroscience Bulletin, 2024)

Distribution, sources and ecological risks of PAHs and n-alkanes in water and sediments of typically polluted estuaries: Insights from the Xiaoqing River - Feifei Zhang; Dong Zhang; Huawei Lou; Xiaoyue Li; Hongrui Fu; Xiaojun Sun; Peiyan Sun; Xinping Wang; Mutai Bao (Journal of Environmental Management, 2024)

Chemodiversity of organic nitrogen emissions from light-duty gasoline vehicles is governed by engine displacements and driving speed - Huixia Han; Hongxuan Du; Shuang Chen; Yisheng Xu; Lihong Ren; Yu Chen; Yeguang Cai; Kexin Wang; Xinping Yang; Mingliang Fu; Yan Ding; Pingqing Fu (Science of The Total Environment, 2024)

Interfacial MoO2 nanograins assembled over graphitic carbon nanofibers boosting efficient electrocatalytic reduction of nitrate to ammonia - Xiu Zhong; Xinping Wu; Yang Liu; Shiqi Yang; Haodong Li; Qian Wang; Danhong Shang; Feng Du; Aihua Yuan; Fu Yang (Journal of Environmental Chemical Engineering, 2024)

Exploitation of function groups in cellulose materials for lithium-ion batteries applications - Yuanyuan Xia; Xinping Li; Jingshun Zhuang; Wenliang Wang; Syed Comail Abbas; Chenglong Fu; Hui Zhang; Ting Chen; Yue Yuan; Xingjin Zhao; Yonghao Ni (Carbohydrate Polymers, 2024)

A metal-phenolic network-assembled nanotrigger evokes lethal ferroptosis via self-supply loop-based cytotoxic reactions - Xinping Zhang; Yuxin Guo; Xiaoyang Liu; Shun-Yu Wu; Ya-Xuan Zhu; Shao-Zhe Wang; Qiu-Yi Duan; Ke-Fei Xu; Zi-Heng Li; Xiao-Yu Zhu; Guang-Yu Pan; Fu-Gen Wu (Chemical Engineering Journal, 2024)

Phase-modulated built-in electric field to boost photogenerated electron migration for efficient dehalogenation - Meng Ren; Pengjie Zhao; Xinping Fu; Meng Liu; Yuting Ning; Yinjie Zhang; Chunyan Wang; Aijun Lin; Jun Cui (Chemical Engineering Journal, 2023)

Reduction potential of vehicular emission in Chengdu, China: A case study of COVID-19 - Xinping Yang; Hefeng Zhang; Wei Li; Hong Tian; Yongdong Wang; Jing Zhou; Ze Bao; Xiaorui Chen; Teng Xiao; Yunjing Wang; Mingliang Fu; Xian Wu; et al. (Urban Climate, 2023)

Exhaust aftertreatment device-derived ammonia emissions from conventional and hybrid light-duty gasoline vehicles over different driving cycles - Han Jiang; Hefeng Zhang; Haiguang Zhao; Mingliang Fu; Yunjing Wang; Xian Wu; Xinping Yang; Jianglin Ji; Hang Yin; Yan Ding (Journal of Hazardous Materials, 2023)

Assessment of eutrophication from Xiaoqing River estuary to Laizhou Bay: Further warning of ecosystem degradation in typically polluted estuary - Feifei Zhang; Hongrui Fu; Huawei Lou; Xiaojun Sun; Dong Zhang; Peiyan Sun; Xinping Wang; Yiming Li; Jinren Lu; Mutai Bao (Marine Pollution Bulletin, 2023)

Antibiotic residues of drinking-water and its human exposure risk assessment in rural Eastern China - Yingying Wang; Xiaolian Dong; Jinxin Zang; Xinping Zhao; Feng Jiang; Lufang Jiang; Chenglong Xiong; Na Wang; Chaowei Fu (Water Research, 2023)

Impacts on real-world extra cold start emissions: Fuel injection, powertrain, aftertreatment and ambient temperature - Xian Wu; Haiguang Zhao; Liqiang He; Xinping Yang; Han Jiang; Mingliang Fu; Hang Yin; Yan Ding (Environmental Pollution, 2023)

Atomic doping modulates the electronic structure of porous cobalt phosphide nanosheets as efficient hydrogen generation electrocatalysts in wide pH range - Yonglong Wang; Bin Li; Weiping Xiao; Xinping Wang; Yunlei Fu; Zhenjiang Li; Guangrui Xu; Jianping Lai; Zexing Wu; Lei Wang (Chemical Engineering Journal, 2023)

Effects of chemical dispersant on the surface properties of kaolin and aggregation with spilled oil - Wenxin Li; Yue Yu; Deqi Xiong; Zhixin Qi; Sinan Fu; Xinping Yu (Environmental Science and Pollution Research, 2022)

Effects of Wave Conditions and Particle Size on the Release of Oil from Oil-Contaminated Sediments in a Wave Tank - Yue Yu; Zhixin Qi; Sinan Fu; Xinping Yu; Wenxin Li; Deqi Xiong (Journal of Marine Science and Engineering, 2019)
The floating oil can drift to the coastal areas and interact with the shoreline substrates after oil spill accidents. This process is demonstrated to be the cause of the formation of oil-contaminated sediments, which has attracted much attention. However, no systematic study has concerned the desorption process of oil from oil-contaminated sediments when the coastal hydrodynamic conditions change. This work determines the effects of wave conditions and particle size on the release of oil from artificially prepared sediments in a wave tank. Nonlinear fitting results show that the oil release kinetic curves can be correctly estimated with the Lagrangian first-order (LFO) first-order equation. Under different test conditions. The oil concentration in the water increases rapidly within 6 h. However, the oil desorption is inhibited thereafter and the process of sorption occurs dominantly. Under higher wave energy, the process of desorption is significantly enhanced and more large oil droplets release from sediments. Under the same wave condition, small oil droplets firstly release from the sediments. Besides, more oil especially with a larger size can release from larger sediment while oil releases more quickly from smaller sediment.

GIS and limit equilibrium in the assessment of regional slope stability and mapping of landslide susceptibility - Tianfeng Gu; Jiading Wang; Xinping Fu; Yaming Liu (Bulletin of Engineering Geology and the Environment, 2015)

Packaging, Amplification, and Appraisal of the Recombinant Tumor-Selective Type I Herpes Simplex Virus Carrying GALV.fus Gene - Zhu Bing; Yang Jianru; Jiang Yuequan; Chen Shifeng; Fu Xinping (Cell Biochemistry and Biophysics, 2014)